2022
DOI: 10.3390/bioengineering9080363
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Equipped Urinary Exosomes Coated Poly (2−ethyl−2−oxazoline)−Poly (D, L−lactide) Nanocarriers for the Pre−Clinical Translation of Breast Cancer

Abstract: Recently, biomimetic nanoparticles for tumor−targeted therapy have attracted intensifying interest. Although exosomes are an excellent biomimetic material, numerous challenges are still hindering its clinical applications, such as low yield, insufficient targeting efficiency, and high cost. In this work, urinary exosomes (UEs) with high expression of CD9 and CD47 were extracted from breast cancer patients by a non−invasive method. Here, a nanotechnology approach is reported for tumor homologous targeting via C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Thus, urinary EVs isolates were able to detect disease-specific molecules undetectable in urine, either because of their low concentration in the bulk fluid or because of their location on EVs [ 21 ]. In fact, EVs could serve as a more specific source for biomarker discovery than unfractionated urine, and provide precision diagnostic information without invasive [ 22 , 23 ]. Previous studies have shown that the biomolecules change at EVs level occurs earlier than that in body fluids [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, urinary EVs isolates were able to detect disease-specific molecules undetectable in urine, either because of their low concentration in the bulk fluid or because of their location on EVs [ 21 ]. In fact, EVs could serve as a more specific source for biomarker discovery than unfractionated urine, and provide precision diagnostic information without invasive [ 22 , 23 ]. Previous studies have shown that the biomolecules change at EVs level occurs earlier than that in body fluids [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Again, doxorubicin was exploited to prove the efficacy of a system aimed at tumor drug delivery for EV-coated polymeric NPs. In this case, as already cited in Section 2.2 for the in vitro tests, the in vivo experiments showed an increased tumor accumulation and tumor growth inhibition in mice, proving the efficacy of the therapy [ 76 ].…”
Section: In Vivo Studiesmentioning
confidence: 66%
“…In this work, the idea was to exploit a body fluid that can be picked up by the patient without invasive processes to obtain tumor-targeting exosomes. In vitro results showed an enhanced rate of apoptosis when employing these nanoconstructs, which was attributed to the increased targeting ability of cancer patient-derived exosomes [ 76 ].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…While loading DOX in SEVs reduces its cardiotoxicity [ 562 , 563 ], it also enhances its efficacy when compared to traditional administration [ 562 , 564 ]. Packaging DOX into SEVs increases its stability, thus allowing a better collection within the tumor [ 564 ] with more limited side toxicity [ 565 ]. It holds the same for PTX, SEVs being more efficient than free PTX and liposomal PTX in inhibiting cancer cell growth [ 566 ].…”
Section: Sevs As Nanovectors To Drive Therapy In Bcmentioning
confidence: 99%